Do education, urbanization, and green growth promote life expectancy? - Haojun Zhang; Yunqiu Zhan; Keqiu Chen (Frontiers in Public Health)
IntroductionEducation (EDU) enhances life expectancy (LEF) by improving health literacy and access to healthcare, leading to healthier lifestyles. Urbanization (URB) fosters better healthcare infrastructure and access to essential services, although it must be managed to avoid negative environmental impacts. Green growth (GG) ensures sustainable development, reduces pollution and environmental risks, and contributes to longer, healthier lives. Therefore, this study examines the impact of EDU, URB and GG on LEF in China from 1990 to 2022.MethodsThis study utilizes the unit root, cointegration test, and Auto Regressive distributed lag (ARDL) model, and for robustness analysis, we use the Fully modified ordinary least squares (FMOLS) and Dynamic ordinary least squares (FMOLS) methods.ResultsThe results show that education, urbanization and green growth have a positive and significant effect on life expectancy, while C02 emissions negatively affect life expectancy.DiscussionThese findings suggest that more resources should be allocated to public education systems to ensure access to quality education from early childhood through higher education and integrate comprehensive health education into school curricula to raise awareness about healthy lifestyles, nutrition, and disease prevention. Promote intelligent urban planning incorporating green spaces, recreational areas, and safe walkways to encourage physical activity and reduce pollution. The findings significantly contribute to health economics and provide a new avenue of research for the academic community and policymakers.